POLITENESS PRINCIPLE IN RADIO DAMAI FM PARIAMAN ADVERTISEMENTS - Nadia Fransisca Dwita; Emidar; Vivi Indriyani; Herlin Triana (Faculty of Letters Universitas Balikpapan, 2024)
Politeness is an important aspect of speaking, especially in mass media. Radio, as an electronic media, conveys information to the public, one of which is advertising. In a radio advertisement, the aim is to be persuasive, so politeness is needed in delivering the broadcast. This article aims to describe the principles of language politeness contained in Radio Damai FM Pariaman advertising broadcasts. This research is qualitative research using descriptive methods. The data in this research are speech sentences in Radio Damai FM Pariaman advertising broadcasts. The data in this study was collected using proficient free-involved listening (SBLC) and note-taking techniques. Data analysis is carried out by transcribing data, identifying data, classifying data, interpreting data, and concluding the results of data analysis. The principles of language politeness contained in Radio Damai FM Pariaman advertising broadcasts are analyzed by classifying each utterance based on the form and function of language politeness and describing the condition of the speech. The results of the research revealed that there were 34 data on the principles of politeness used in Radio Damai FM Pariaman advertising broadcasts. This research has implications for Indonesian language learning in schools, especially advertising texts.